Impact of Highly Saturated versus Unsaturated Fat Intake on Carbohydrate Metabolism and Vascular Reactivity in Rat - Youzan Ferdinand Djohan; Fabrice Raynaud; Karen Lambert; Jean-Paul Cristol; Charles Coudray; Christine Feillet-Coudray; Anne Virsolvy; Eric Badia (Biochemistry Research International)
Palm olein (PO) and lard are considered harmful to health because of their highly saturated fatty acid content. On the contrary, olive oil (OO) with its high level of polyunsaturated fatty acids is considered healthier. This study aims to evaluate the effects of high consumption of these oils on carbohydrate metabolism and vascular function. Male Wistar rats were fed ad libitum for 12 weeks with different high fat diets (HFD) containing 30% of each oil. Systemic glycemia, insulinemia, and lipidemia were assessed by routine methods or by ELISA. GLUT4 muscular expression and hepatic and muscular Akt phosphorylation were analyzed by western blot. Vascular function was evaluated, ex vivo, on aortic rings and on the variations of isometric tensions. The results show that fasting blood glucose was increased with PO and OO diets and decreased with lard. Compared to control diet, this increase was significant only with PO diet. The area under the curve of IPGTT was increased in all HFD groups. Compared to control diet, this increase was significant only with PO. In contrast, stimulation of the pathway with insulin showed a significant decrease in Akt phosphorylation in all HFD compared to control diet. KCl and phenylephrine induced strong, dose-dependent vasoconstriction of rat aortas in all groups, but KCl EC50 values were increased with lard and OO diets. The inhibitory effect of tempol was absent in PO and lard and attenuated in OO. Vascular insulin sensitivity was decreased in all HFD groups. This decreased sensitivity of insulin was more important with PO and lard when compared to OO diet. In conclusion, the results of this study clearly show that high consumption of palm olein, olive oil, and lard can compromise glucose tolerance and thus insulin sensitivity. Furthermore, palm olein and lard have a more deleterious effect than olive oil on the contractile function of the aorta. Excessive consumption of saturated or unsaturated fatty acids is harmful to health, regardless of their vegetable or animal origin.